The Siyasah Dusturiyyah Perspective on Personal Data Protection in Digital Public Services in Bandung Kidul District, Bandung City, Under Law Number 27 of 2022 - Dwi Pandu Wijaksana; Yana Sutiana; Taufiq Alamsyah (Journal of Indonesian Islamic Studies, 2026)
This study examines the implementation of personal data protection in digital public services at Bandung Kidul District, Bandung City, based on Law Number 27 of 2022 concerning Personal Data Protection from the perspective of Siyāsah Dustūriyyah. The research employs an empirical juridical approach using a case study method with a descriptive, analytical, and evaluative design. The findings indicate that Bandung Kidul District has implemented personal data protection through standard operating procedures (SOPs) for data management, awareness programs for government personnel, the provision of information to the public prior to data collection, and mitigation procedures in the event of a data breach. However, the implementation has not yet been fully effective due to several constraints, including limited technological infrastructure, budgetary resources, and human resource capacity. From the perspective of Siyāsah Dustūriyyah, personal data protection constitutes part of the government's fiduciary responsibility (amanah) to safeguard the public interest (maslahah) and to protect citizens' dignity and property. Therefore, strengthening technical regulations, enhancing the capacity of government officials, and providing adequate supporting infrastructure are essential to ensure the effective implementation of personal data protection at the district level..